2001
DOI: 10.1002/ccd.1310
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter treatment of coronary artery disease and atrial septal defect with sequential implantation of coronary stent and Amplatzer septal occluder: Preliminary results

Abstract: Coronary stent implantation had been established as a highly effective revascularization technique in patients with occlusive coronary artery disease. Transcatheter closure of atrial septal defects is becoming a definite alternative to surgery in properly selected patients. During a 19-month period, 6 patients (50% women; mean age, 58 +/- 17 years; range, 32-73 years) of a consecutive series of 176 prospective multicenter registry patients undergoing transcatheter atrial septal defect closure were treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…5,6) Onorato, et al reported successful sequential percutaneous coronary intervention (PCI) for CAD and transcatheter ASD closure in 6 cases with angina pectoris, where four patients underwent PCI prior to ASD closure. 13) Tomai, et al reported an unsuccessful case that developed acute left HF after a simultaneous approach of PCI and transcatheter ASD closure. 4) They proposed possible reasons for the development of acute left HF such as myocardial stunning following PCI adding to the mildly reduced LVEF at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) Onorato, et al reported successful sequential percutaneous coronary intervention (PCI) for CAD and transcatheter ASD closure in 6 cases with angina pectoris, where four patients underwent PCI prior to ASD closure. 13) Tomai, et al reported an unsuccessful case that developed acute left HF after a simultaneous approach of PCI and transcatheter ASD closure. 4) They proposed possible reasons for the development of acute left HF such as myocardial stunning following PCI adding to the mildly reduced LVEF at the baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Very few reports of combined percutaneous procedure are available in the literature. Sequential ASD device closure and PTCA have been reported with ASD closure before [5] or after [6] PTCA. Successful combined procedure was later reported by Yalonetsky et al [7].…”
Section: Discussionmentioning
confidence: 99%
“…As a result of the frequent coexistent coronary atherosclerosis, combined intervention of percutaneous revascularization and transcatheter closure could be a good treatment option. 30 Transcatheter closure of patent ductus arteriosus with ϾAmplatzer Occluder devices or detachable coils is effective in the elderly because they avoid morbility associated with surgery 31 ; care should be taken in the case of very enlarged or heavily calcified ductus, which are relative contraindications for transcatheter closure. Although technically difficult, surgical repair has low mortality and excellent follow up in patients Ͼ50 years, especially with Qp/Qs Ͼ 1.5 and pulmonary pressure Ͻ75 mm Hg.…”
Section: Discussionmentioning
confidence: 99%